Fire-retardant materials containing fibers
The introduction of a fiber-containing fireproof material with enhanced compressibility and mechanical strength addresses the brittleness issue of existing materials, ensuring consistent fire-resistant performance throughout the life of lithium-ion batteries.
Patent Information
- Application Number
- JP2024550124
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-24
- Filing Date
- 2023-02-23
- Publication Date
- 2025-03-21
AI Technical Summary
Existing fireproofing materials for lithium-ion batteries are brittle and prone to damage due to the expansion and contraction of battery cells, leading to a loss of fire-resistant properties over time.
A fireproof material containing fibers with sufficient compressibility and mechanical strength to maintain thermal properties from the early life to the end life of lithium-ion batteries, composed of a fiber matrix with additives that enhance flame retardancy, low thermal conductivity, and electrical insulation.
The fiber-containing fireproof material effectively suppresses thermal runaway and maintains its fire-resistant properties throughout the life of the battery, even under compression, thereby preventing damage and ensuring safety.
Smart Images

Figure 2025507670000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims priority to U.S. Provisional Application No. 63 / 268,434, filed February 24, 2022, entitled "Fire-Resistant Material Comprising Fibers," which is incorporated by reference in its entirety.
[0002] The present disclosure relates to compositions comprising fibers for fire protection between lithium ion batteries, the fire protection material comprising the fibers being compressible such that the fire protection properties are maintained even as the lithium ion batteries swell over time. [Background technology]
[0003] Lithium-ion batteries (LiBs) are increasingly being used in various industries, including electric vehicles (EVs), due to their high energy density and cycling characteristics. LiB cells have the disadvantage of being prone to thermal runaway, where the failure of a single cell can propagate to surrounding cells and cause the LiB to catch fire.
[0004] Typically, fire-resistant materials are brittle and inflexible, meaning that many will fracture when exposed to stresses such as shock or vibration. This is problematic for LiB applications because LiB cells expand during cycling and over time. Hence, there is a need for fire-resistant materials that can maintain low thermal conductivity over the life of the LiB. [Brief description of the drawings]
[0005] Various embodiments of the present disclosure will become more fully understood from the detailed description set forth below and the accompanying drawings, in which like reference numbers may indicate identical or functionally similar elements. The embodiments will now be described in detail with reference to the accompanying figures, in which the following embodiments are as follows: [Figure 1] FIG. 1 shows a prior art fire protection material placed between lithium ion batteries. [Diagram 2] FIG. 2 is a fire-resistant material including fibers according to an embodiment of the present disclosure. [Diagram 3] FIG. 3 is a fire-resistant material including fibers according to an embodiment of the present disclosure. [Figure 4] FIG. 4 shows a fire-blocking material including fibers according to an embodiment of the present disclosure disposed between lithium-ion batteries. [Diagram 5] FIG. 5 is a graph comparing the compressive strain measured in Example 1 and Comparative Example 1. [Figure 6] FIG. 6 is a graph comparing the compressive strain measured in Example 2 and Comparative Example 2. [Figure 7] FIG. 7 is a graph comparing the compressive strain measured in Example 3 and Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0006] The following disclosure provides many different embodiments or examples. To simplify the disclosure, specific examples of components and arrangements are described below. Of course, these are merely illustrative and are not intended to be limiting. Furthermore, the disclosure may repeat reference numerals and / or letters in various examples. This repetition is for simplicity and clarity and does not in itself dictate a relationship between the various embodiments and / or configurations discussed.
[0007] 1, existing fire-resistant composites 12 are brittle and, when placed in the gap between lithium-ion cells 14a, 14b, can be damaged by the expansion of the cells 14a, 14b and the resulting closure of the gap. As the cells 14a, 14b expand and contract during cycling, this damage to the fire-resistant composite 12 can cause the fire-resistant composite 12 to collapse such that areas within the gap are no longer covered by the fire-resistant composite 12. This is especially true in high impact applications such as electric vehicles, as the vibration and movement of the electric vehicle accelerates the collapse of the fire-resistant composite 12.
[0008] According to an embodiment of the present disclosure, a fire-resistant material is provided that includes fibers having sufficient compressibility and mechanical strength to maintain thermal properties from the beginning of life (BoL) to the end of life (EoL) of a LiB. As used herein, EoL refers to the end of the service life of a battery that includes the fire-resistant material, at which the capacity is reduced to the point where the battery needs to be replaced. This point can be, for example, after a set number of cycles (e.g., 1,000 cycles, 5,000 cycles, or 10,000 cycles), after a set number of years of operation of the battery (e.g., 2 years, 5 years, 8 years, or 10 years), after a set number of miles driven in an electric vehicle using the battery (e.g., 50,000 miles, 100,000 miles, 200,000 miles, or 250,000 miles), after the capacity is reduced to below a set percentage of the battery's peak capacity (e.g., 85%, 80%, 75%, 70%, 65%, 60%, 50%, 40%, or 30% of peak capacity), or a combination of these thresholds. For example, in some embodiments, the EoL can be set as the earliest of when an EV using the battery reaches 10,000 miles, 8 years, or when the battery falls below 70% of its peak capacity. Maintaining sufficient compressibility and mechanical strength from BoL to EoL avoids the collapse problems discussed above and allows fire-resistant materials to inhibit thermal runaway throughout the life of the LiB.
[0009] Flammable The fire-retardant materials of the present disclosure are flame-retardant and, when employed in a LiB, can help reduce the spread of flame between cells of the LiB. In some embodiments, the fire-retardant materials are classified as V-2, V-1, V-0, 5VB, or 5VB materials under UL94. In some embodiments, the fire-retardant materials are flame-retardant (i.e., do not melt) at temperatures of at least 600 degrees Celsius, at least 700 degrees Celsius, at least 800 degrees Celsius, at least 900 degrees Celsius, at least 1000 degrees Celsius, at least 1100 degrees Celsius, at least 1150 degrees Celsius, at least 1200 degrees Celsius, at least 1250 degrees Celsius, at least 1260 degrees Celsius, or at least 1300 degrees Celsius. In some embodiments, the fire-retardant materials are certified as flame-retardant under UL723, ASTM E84, ASTM 136, ASTM E1529, and / or UL 1709. In some embodiments, the fire-resistant material is rated A2-s1, d0 or higher under EN13501-1.The fire-resistant material may exhibit any one or more of the aforementioned characteristics at both the BoL of the battery containing the fire-resistant material and the EoL of the battery.
[0010] Thermal Conductivity The fire-resistant materials of the present disclosure have low thermal conductivity, allowing the material to be as thin as possible while consuming minimal space in a LiB battery pack. This allows manufacturers to minimize the size of the pack (containing multiple batteries) and maximize the energy density of the pack. In some embodiments, the fire-resistant materials have a thermal conductivity (measured according to ASTM C201) of at most 0.10, at most 0.08, at most 0.06, at most 0.05, at most 0.04, at most 0.035, at most 0.03, at most 0.02, at most 0.015, at most 0.01 W / m·K at 0° C., 10° C., 20° C., 30° C., 40° C., 50° C., 60° C., 70° C., 80° C., 90° C., and / or 100° C. In some embodiments, the fire-resistant material exhibits a thermal conductivity at 100 degrees Celsius, 200 degrees Celsius, 300 degrees Celsius of at most 0.14, at most 0.12, at most 0.10, at most 0.08, at most 0.07, at most 0.05, at most 0.04, at most 0.035, at most 0.03, at most 0.025, at most 0.02, at most 0.015, or at most 0.01 W / m·K at 100 degrees Celsius, 200 degrees Celsius, 300 degrees Celsius, 400 degrees Celsius, 500 degrees Celsius, 600 degrees Celsius, 700 degrees Celsius, 800 degrees Celsius, 900 degrees Celsius, and / or 1000 degrees Celsius. The fire-retardant material may exhibit any one or more of the aforementioned characteristics at both the BoL of a battery containing the fire-retardant material and at the EoL of the battery.
[0011] Electrical Conductivity The fire-resistant materials of the present disclosure have low electrical conductivity, which can reduce the incidence of thermal runaway (often caused by internal and external short circuits). The fire-resistant materials can maintain this property even after thermal runaway. In some embodiments, the fire-resistant materials have a dielectric strength of at least 5 kV / mm, at least 6 kV / mm, at least 7 kV / mm, at least 8 kV / mm, between 5 kV / mm and 15 kV / mm, between 6 kV / mm and 12 kV / mm, or between 7 kV / mm and 10 kV / mm, as measured under ASTM 149-Method C. The fire-resistant materials can exhibit the aforementioned properties at both the BoL of the battery containing the fire-resistant material and the EoL of the battery.
[0012] Compressibility The fire-resistant material of the present disclosure has controlled compression properties that allow it to have good flame retardancy, low thermal conductivity, and low electrical conductivity even under compression. In some embodiments, the fire-resistant material maintains or improves its flame retardancy, thermal conductivity, and / or electrical conductivity under compression. Such controlled compression properties limit damage to the typically brittle fire-resistant material as the cell maintains load when installed in the LiB pack and expands over time. In some embodiments, the fire-resistant material has a compression recovery measured according to ASTM D3574-Test C of at least 50%, at least 55%, at least 60%, at least 65%, at least 70%, or at least 75% at the BoL of the LiB. In some embodiments, the fire-resistant material has a compression recovery of at least 5%, at least 10%, at least 15%, at least 20%, at least 25%, or at least 30% at the EoL of the LiB.
[0013] The compressive strain of the fiber-containing fire-resistant material can be measured over a range of compression speeds from 1 mm / min to 100 mm / min (typically tested according to ASTM D3574). The material can be cut into 50 mm x 50 mm squares and compressed between two parallel plates at ambient pressure and temperature. Compression curves can be generated from strains from 0% to 80% typical EoL values found in LiBs. In some embodiments, the fire-resistant material has a compressive strain at 60% compression in the range of 50 kPa to 2,500 kPa, at 70% compression in the range of 200 kPa to 4,000 kPa, and at 80% compression in the range of 1,000 kPa to 8,000 kPa. In some embodiments, the fire-resistant material has a compressive strain of at least 100 kPa or at least 200 kPa throughout the 20-50% compression range.
[0014] Explosion Resistance Thermal runaway in an EV battery pack is not a gentle, controlled event. It can result in violent outbursts of gas, flames, or even particulate ejection from within the battery. This calls for insulating materials within the battery pack to act as explosion protection. Such materials can be placed, for example, between the top of the battery array and the pack lid, or between the individual cells of the battery pack. Such materials must be able to remain intact and maintain their insulating properties even when exposed to high pressure flames and particulates.
[0015] According to some embodiments, the fire-resistant material may be an explosion-resistant material. Blast resistance generally refers to the ability of a material to withstand thermal and mechanical forces, and can be tested, for example, by subjecting the material to a torch (e.g., about 1100 degrees Celsius) and feeding alumina grit through the torch. It is desirable for an explosion-resistant material to remain intact for a predetermined period of time while maintaining a cold surface temperature below a set threshold.
[0016] 2, in one or more embodiments, the fire-resistant material 100 may be comprised of a fiber matrix 110 having one or more additives 120, 130 dispersed or suspended therein. The fiber matrix 110 includes fibers having an aspect ratio of at least 3. The fiber matrix 110 may be comprised of a single type of fiber or a combination of different types of fibers. Suitable fibers that may be included in the fiber matrix 110 include microglass fibers, low biopersistent fibers (LBP), refractory ceramic fibers (RCF), and / or polycrystalline wool (PCW).
[0017] The microglass fibers may include A-glass, B-glass, C-glass, and / or E-glass fibers. In some embodiments, the microglass fibers have an average diameter of about 0.25 micrometers to about 5 micrometers. In other embodiments, the microglass fibers have a diameter of at least about 3 micrometers, at least about 4 micrometers, at least about 5 micrometers, or at least about 6 micrometers.
[0018] Suitable LBP fibers include alkaline earth silicate (AES) fibers as described in U.S. Patent Nos. 8,663,774 and 8,551,897, each of which is incorporated herein by reference in its entirety. Useful LBP fibers are commercially available from Alkegen, Inc. (Tonawanda, NY) under the registered trademark INSULFRAX®. INSULFRAX® fibers generally consist of the fiberization product of about 61 to about 67% by weight silica, about 27 to about 33% by weight calcia, and about 2 to about 7% by weight magnesia.
[0019] Refractory ceramic fibers (RCFs) comprise alumina and silica. In some embodiments, the RCFs may comprise about 50% alumina by weight. In some embodiments, the RCFs may comprise about 45 to about 60% alumina by weight and about 40 to about 55% silica by weight. In some embodiments, the RCFs may comprise about 29 to about 31% alumina by weight, about 53 to about 55% silica by weight, and about 15 to about 17% zirconia by weight. In some embodiments, the RCFs may have an average length ranging from about 3 to about 6.5 mm, typically less than about 5 mm, and an average fiber diameter ranging from about 0.5 μm to about 145 μm. Useful RCFs are commercially available from UNifrax LLC (Niagara Falls, NY) under the registered trademark FIBERFRAX®. The FIBERFRAX® ceramic fibers comprise the fiberized product of a melt consisting of about 45 to about 75% alumina and about 25 to about 55% silica by weight. The FIBERFRAX® fibers exhibit an operating temperature of up to about 1540 degrees Celsius and a melting point of up to about 1870 degrees Celsius.
[0020] PCW is an aluminosilicate fiber having an alumina content of greater than 70% by weight, or from about 72 to about 96% by weight. PCW is mechanically strong and, when included, may reduce the brittleness (and resulting loss of material during vibration) of the fire-resistant material 100. In some embodiments, the PCW has an average diameter of at least about 3 micrometers, at least about 4 micrometers, at least about 5 micrometers, or at least about 6 micrometers. In some embodiments, a suitable PCW comprises alumina fibers sold under the trade name SAFFIL® available from Unifrax LLC (Tonawanda, NY). In some embodiments, the PCW may comprise alumina fibers as described in U.S. Pat. Nos. 4,792,478 and 5,176,857, each of which is incorporated herein by reference in its entirety.
[0021] Other fibers that may be included in the fiber matrix 110 include silica threads (connected or chopped) and / or organic fibers such as nylon fibers, polyvinyl alcohol (PVA) fibers, aramid fibers, polyester fibers, etc. In some embodiments, the fiber matrix 110 has long fibers having an average length of at least about 5 mm, at least about 10 mm, at least about 25 mm, at least about 40 mm, at least about 50 mm, at least about 70 mm, or at least about 100 mm. In some embodiments, the fiber matrix has a woven material that can help trap additives 120, 130 within the fiber matrix 110.
[0022] In one or more embodiments, each of the aforementioned fibers can comprise up to 100% by weight of the fiber matrix 110. In some embodiments, the fiber matrix 110 has microglass or LBP fibers in an amount of at least 50% by weight, and up to 50% by weight of long and / or strong fibers selected from PCW, silica yarn, and / or organic fibers. In such embodiments, the strong fibers can have an average diameter of at least about 3 micrometers, at least about 4 micrometers, at least about 5 micrometers, or at least about 6 micrometers. In some embodiments, the fiber matrix 110 has LBP fibers as primary fibers (at least 50% by weight). In other embodiments, the fiber matrix 110 has microglass fibers as primary fibers due to their excellent insulating properties.
[0023] In some embodiments, the fire-resistant material 100 is in the form of paper and has a thickness of greater than about 0.1 mm to about 10 mm, about 1 mm, about 2 mm, or about 3 mm. In some embodiments, the fire-resistant material 100 has a basis weight of about 40 gsm (grams per square meter) to about 3000 gsm, about 100 gsm to about 2500 gsm, about 200 gsm to about 1500 gsm, about 100 gsm, about 200 gsm, about 300 gsm, or about 400 gsm. In some embodiments, the fire-resistant material has a basis weight of about 50 kg / m 3 ~about 500kg / m 3 , about 100kg / m 3 ~about 350kg / m 3 , or about 100 kg / m 3 ~about 250kg / m 3 has a density of
[0024] In some embodiments, the additives 120, 130 can have organic binders that maintain the flexibility of the fire-resistant material 100 and contribute adhesive strength to maintain the position of the fire-resistant material 100 during normal operation of an apparatus using the material (e.g., withstanding vibrational forces in an EV LiB). In some embodiments, the additives 120, 130 positively affect one or more properties of the fire-resistant material 100. For example, in some embodiments, the additives 120, 130 can reduce the thermal conductivity, increase the dielectric strength, and / or increase the compressive set of the fire-resistant material 100.
[0025] In some embodiments, the binder material comprises latex, cellulose, silicone, PVA, polyester, or a combination thereof. In some embodiments, the binder comprises organic fibers. In such embodiments, the fire-resistant material 100 may be heat pressed to at least partially melt the organic fibers and bond the materials. In some embodiments, the binder is present in an amount of about 0.5% to about 10% by weight, about 1% to about 20% by weight, or about 5% to about 15% by weight, based on the total weight of the fire-resistant material 100.
[0026] In some embodiments, the additives 120, 130 comprise microporous materials, platelets, aerogels, mica, microspheres, intumescent materials, opacifying or opacifying agents, heat absorbing materials, phase change materials, or other inorganic fillers that help to increase the thermal conductivity performance of the fire-resistant material 100 compared to the fiber matrix 110 alone. Suitable opacifying agents include, but are not limited to, silicon carbide, graphite, TiO2, Fe2O3, and ilmenite. These opacifying agents act to block IR radiation passing through the fire-resistant material 100, which becomes a large component of heat transfer as the temperature increases. The additives 120, 130 allow the fire-resistant material 100 to have a smaller paper thickness, leaving more space for the battery (i.e., increasing energy density) or reducing the overall size of the battery pack.
[0027] The microporous material has a thickness of at least about 100 m 2 / g, at least about 200m 2 / g, or at least 300m 2 The microporous material may have a surface area of about 1 nm to about 500 μm, about 50 nm to about 50 μm, or about 1 μm to about 5 μm. Suitable inorganic fillers include silica materials, such as fumed silica, precipitated silica, silica gel, silica aerogel, alumina materials, zirconia materials, titania materials, or combinations thereof. The inorganic filler may have a chemically modified surface that imparts hydrophobicity. For example, the inorganic filler may have a hydrophobizing agent on its surface. Suitable hydrophobizing agents include those having the chemical formula R, such as methyldichlorosilane, dimethyldichlorosilane, ethyltrichlorosilane, and diethyldichlorosilane. n Six 4-n Organic halosilanes, such as ethyltriethoxysilane, have the chemical formula R n Si(OR) 4-nsilanes having the chemical formula R, such as, but not limited to, hexadecyltrimethoxysilane, methylsilane, dimethylsilane, trimethylsilane, ethylsilane, and diethylsilane. n SiH 4-n Organosilanes, such as triethylsilane, have the formula R n Si(OR) 4-n Organosilanes of the formula R, such as triethylsilane, chlorodimethylsilane, and chloro(ethoxy)(methyl)silane. n SiH m X 4-(m+n) Organo-H-halosilanes and organo-H-alkoxysilanes. Suitable platelets include, but are not limited to, coated or uncoated vermiculite, mica, clay, and talc platelets. Suitable micas include, but are not limited to, muscovite, phlogopite, biotite, lepidolite, glauconite, paragonite, and zinnwaldite, and may include synthetic micas such as fluorophlogopite. Clay platelets that may be used include, but are not limited to, ball clay, bentonite, smectite, hectorite, kaolinite, montmorillonite, saponite, sepiolite, sauconite, or combinations thereof. In some embodiments, mica, whether in platelet form or not, may be included in the fire-resistant material 100 to provide improved blast resistance. In some embodiments, the microporous material may include an anisotropic material having thermal conductivity that varies with its orientation. In some embodiments, the microporous material may include a smoke-producing material.
[0028] Any one or more of the microporous materials, platelets, aerogels, mica, microspheres, effusive materials, endothermic materials, phase change materials, or other inorganic fillers described above can be included in the fire-resistant material 100 in an amount of from greater than 0% to about 60% by weight, from greater than about 0.1% to about 50% by weight, from greater than about 5% to about 30% by weight, or from greater than about 10% to about 25% by weight, based on the total weight of the fire-resistant material 100.
[0029] In some embodiments, the fire-resistant material 100 includes a compression additive, which may be included as an additive 120, 130 encapsulated in the fiber matrix 100 or may be included as a layer adhered to the fiber matrix 110. The compression additive may include a foam, such as an open or closed cell foam formed from polyurethane, polyethylene, ethylene propylene diene monomer (EPDM), polyethylene terephthalate (PET), silicone, and the like. In some embodiments, the compression additive is a paper, such as an organic fiber paper (e.g., formed from nylon). In some embodiments, the compression additive is an organic fiber, as described above. In some embodiments, the compression additive may include an acrylic latex. In some embodiments, the compression additive may be present in an amount of about 2% to about 50% by weight, at least about 2% by weight, at least about 5% by weight, at least about 10% by weight, at least about 15% by weight, at least about 20% by weight, at most about 50% by weight, at most about 40% by weight, at most about 30% by weight, or at most about 25% by weight, based on the total weight of the fire-resistant material 100.
[0030] In some embodiments, the fire-resistant material 100 includes a compression additive, which may be included as an additive 120, 130 encapsulated in the fiber matrix 100 or may be included as a layer adhered to the fiber matrix 110. The compression additive may include a foam, such as an open or closed cell foam formed from polyurethane, polyethylene, ethylene propylene diene monomer (EPDM), polyethylene terephthalate (PET), silicone, or the like. In some embodiments, the compression additive is a paper, such as an organic fiber paper (e.g., formed from nylon). In some embodiments, the compression additive is an organic fiber, as described above. In some embodiments, the compression additive may include an acrylic latex. In some embodiments, the compression additive may be present in an amount of about 2% to about 50% by weight, at least about 2% by weight, at least about 5% by weight, at least about 10% by weight, at least about 15% by weight, at least about 20% by weight, at most about 50% by weight, at most about 40% by weight, at most about 30% by weight, or at most about 25% by weight, based on the total weight of the fire-resistant material 100.
[0031] In one or more embodiments, the fire-blocking material 100 may be formed by dry-laying, batch sheeting, or paper-making techniques, including processes using delta formers, rotoformers, fordiniers, or cylinder machines. In some embodiments, the fire-blocking material 100 may be formed using a dry-laying technique that does not use a binder, which may optionally include a needle step. In such embodiments, the fire-blocking material 100 may include long fibers having a length of at least 10 mm (e.g., 20-30 mm), which may be continuous or discontinuous. In some embodiments, the fire-blocking material 100 may be formed using a wet-laying process, in which the additives 120, 130 include a binder that is well dispersed within the fiber matrix 110, and whose migration is controlled using a controlled drying system, such as a convection oven, radio frequency (RF), and / or microwave dryer. In some embodiments, a heated drum can be used to limit migration (e.g., using alternate side heating or staged heating) or to purposefully migrate materials so that selected components are optionally directed toward or away from adjacent cells to maximize protection. Inorganic materials, such as those added as a gel phase, can migrate and be used on the hot side of an application to provide additional protection. In some embodiments, organic materials can migrate away from the core of the material to improve thermal performance at low temperatures (i.e., normal operating temperatures) and improve adhesion of optional tape backing or laminate layers. In some embodiments, drying methods can control migration of organic binders to distribute the same evenly through the thickness of the fire-resistant material 100.
[0032] In some embodiments, the fire-resistant material 100 has about 0.1% to about 50% by weight of long fibers in the fiber matrix 110 and does not include an organic binder material. In such embodiments, the long fibers can provide a structural framework that allows the wet-laid product to be flexible in the absence of an organic binder material. In some embodiments, the fire-resistant material 100 does not include an organic binder and is manufactured using different vacuum pressures in forming the wet-laid sheet to affect the density of the resulting wet-laid sheet. In some embodiments, the fire-resistant material 100 has a density of at most 10 g / cm 3 , at most 7g / cm 3 , at most 5g / cm 3 , at most 4g / cm 3 , at most 2g / cm 3 , at most 1g / cm 3 , at most 0.5g / cm 3 , at least 0.025 g / cm 3 , at least 0.05g / cm 3 , at least 0.1 g / cm 3 , at least 0.25 g / cm 3 , at least 0.5g / cm 3 , at least 1g / cm 3 , or any logical combination of the upper and lower limits mentioned above (e.g., 0.025 g / cm 3 , at least 0.05g / cm 3 , at least 0.1 g / cm 3 , at least 0.25 g / cm 3 , at least 0.5g / cm 3 , at least 1g / cm 3 ), 0.025g / cm 3 ~5g / cm 3 , or 0.1 g / cm 3 ~5g / cm 3 ).
[0033] In some embodiments, the fire-resistant material 100 can be formed into complex three-dimensional shapes rather than a flat sheet. For example, the fire-resistant material 100 can be molded, either by press forming or vacuum forming, to the shape of a battery lid, shroud, or spacing between cells.
[0034] In any embodiment, the fire-resistant material 100 can include a tape backing (not shown). The tape backing can provide reinforcement if a cell is broken and is required to have some degree of explosion resistance to help slow fire spread between cells. In some embodiments, the tape backing can have a thickness of about 10 μm to about 1 mm, about 10 μm to about 700 μm, about 10 μm to about 400 μm, about 10 micrometers, about 20 micrometers, about 30 micrometers, about 40 micrometers, about 50 micrometers, about 60 micrometers, about 70 micrometers, about 80 micrometers, about 90 micrometers, or about 100 micrometers. The tape backing can be directly adhered to the fire-resistant material 100 (paper) using a hot melt adhesive or a pressure sensitive adhesive. In some embodiments, the tape backing can be a scrim of organic foil (such as made of polypropylene, polyethylene terephthalate, polytetrafluoroethylene, etc.) or metal foil (such as made of Al, Sn, Cu, etc.) In some embodiments, the tape backing can have mica to improve the blast resistance of the fire retardant material 100.
[0035] In some embodiments, the fire-resistant material 100 is comprised, based on the total weight of the fire-resistant material 100, as follows: The inorganic fibers are contained in an amount of 10 to 95% by weight, 10 to 90% by weight, 20 to 90% by weight, 30 to 80% by weight, 40 to 80% by weight, 40 to 70% by weight, 40 to 60% by weight, at least 20% by weight, at least 30% by weight, at least 40% by weight, at least 50% by weight, at least 60% by weight, or at least 70% by weight. The microporous material, platelets, aerogels, mica, microspheres, effusive materials, opacifying agents or opacifiers, heat absorbing materials, phase change materials, other inorganic fillers, or combinations thereof, are present in an amount of 0-60%, 0.1-50%, 5-30%, 10-25%, at least 1%, at least 5%, at least 10%, at least 20%, at least 30% by weight. The compression additive is present in an amount of 0-50%, at least 2%, at least 5%, about 10%, at least 15%, at least 20%, at most 50%, at most 40%, at most 30%, or at most 25% by weight. - Contains 1-20 wt. %, 5-15 wt. %, at least 2 wt. %, at least 5 wt. %, or at least 10 wt. % of said binder (inorganic, organic, or a combination thereof).
[0036] In any embodiment, the fire-resistant material 100 may include an explosion-resistant coating. In some embodiments, the coating may have a thickness of up to 20 mm, up to 10 mm, up to 5 mm, 0.05-20 mm, 0.1-10 mm, or 0.1-5 mm.
[0037] In some embodiments, the explosion-resistant coating is applied as a viscous dispersion or gel of hydrated inorganic materials that dry to form a protective surface. Examples of inorganic materials include bentonite clay and dispersible Al2O3 (e.g., colloidal alumina). Without being bound by theory, it is believed that the surface hydroxyl groups of these materials allow for interparticle adhesion upon drying, resulting in a hard, rigid surface coating that can withstand impacts from small particles, even when exposed to flames as hot as 1100 degrees Celsius. This not only leaves the barrier intact, but also protects the insulating layer of the fire-resistant material 100 and prevents the diffusion of thermal events.
[0038] In some embodiments, the explosion-resistant coating comprises a silicone blend. The silicone blend coating allows the fire-resistant material 100 to remain flexible throughout the manufacturing process. In a thermal runaway situation, the silicone blend coating is immediately exposed to extreme temperatures, causing the coating to oxidize and ceramize into a hard, rigid layer that can withstand impact from particulates. In some embodiments, the silicone blend comprises a crosslinked system of polysiloxanes, such as poly(dimethylsiloxane), poly(diphenylsiloxane), poly(methylphenylsiloxane), and copolymers thereof. The silicone blend may also comprise at least one inorganic additive or filler. Such additives and fillers include, but are not limited to, heat-absorbing materials (e.g., aluminum trihydroxide, magnesium hydroxide, CaCO3), smoke-producing additives (e.g., expandable vermiculite, CaCO3), fluxing agents (e.g., glass frit, zinc borate), reinforcing additives (e.g., glass fiber, wollastonite, mica), aerogels, or combinations thereof. The additives and fillers help to form a strong ceramic layer when the coating is fired. For example, in silicone blends that contain fluxing agents, the fluxing agents can cause melting of the surface of the silicone blend or fibers within the fire-resistant material 100. This bonds the network to the silicone oxide (SiO2) to form an extended, rigid coating and helps prevent cracking. The blended resinous silicone coating can be applied by spray for low viscosity blends or by roller coating equipment, blade coaters, or slot die coaters for low to high viscosity blends. Silicones using room temperature vulcanizing (RTV) chemistry can be vulcanized for up to 24 hours, and the vulcanization rate can be accelerated by humidity, elevated temperature, or the use of an appropriate catalyst. Low temperature vulcanizing (LTV) silicones utilize peroxide radical initiators and vinyl, acrylate, and methacrylate silicone pendant functional groups to cure at slightly higher temperatures in as little as 10 hours. The cure temperature of LTV silicones ranges from 30 to 250 degrees Celsius, depending on the activation temperature of the catalyst.Alternatively, a UV-activated radical initiator can be used which cures the resin with a UV lamp.
[0039] Turning to FIG. 3, in some embodiments, the fire-resistant material 200 may be a laminate having a compressible layer 220 and one or more fire-resistant layers 210a, 210b. In some embodiments, one or more fire-resistant layers 210a, 210b may be the same as the fire-resistant material 100 described above. In one or more embodiments, the compressible layer 220 has the same material as the compressible additive described above. The compressible layer 220 may be adhered to the one or more fire-resistant layers 210a, 210b using a hot melt adhesive or a pressure sensitive adhesive. In some embodiments, either the compressible layer 220 and one or more fire-resistant layers 210a, 210b may include a tape backing as described above. In some embodiments, the compressible layer 220 does not include inorganic fibers. In some embodiments, the compressible layer 220 has the compressible additive.
[0040] The laminated configuration of the fire-blocking material 200 optimizes the material's compressibility as the environment changes in a battery pack consisting of multiple cells. Cells are known to expand during use, leading to a reduction in the gap size that can compress and damage the fire-blocking material. Some compression is necessary to ensure that the material stays in place (i.e., does not slump) in vibratory applications such as EV applications. As shown in FIG. 4, when the fire-blocking material 200 is used between LiB cells, the expansion of the cells does not damage the fire-blocking material 200 due to its compressive properties. Although not shown, the fire-blocking material 100 can achieve results similar to those shown in FIG. 4.
[0041] In some embodiments, the fire-resistant material is formed as a fire-resistant film. The fire-resistant film may be a thin film that can be dipped and sprayed onto the battery pack case to provide thermal and electrical protection. The fire-resistant film is formed from fibers, such as those described above for the fiber matrix 110, and additives, such as the additives 110, 120, described above. In some embodiments, the fire-resistant film can be prepared using a mixer (dry or wet, low shear or high shear, etc.). In some embodiments, the fire-resistant film includes colloids and / or other inorganic binders and organic binding agents, such as latex and / or cellulose. In any embodiment, the fire-resistant film may be formed as a wet solution that is dried onto a surface (e.g., the surface of a cell or battery pack or other substrate).
[0042] In some embodiments, the fire-resistant film may be applied onto a tape backing as described above. In such embodiments, the fire-resistant film may be applied to the tape backing by spraying, roller, or dip coating a solution of fibers and additives including cellulose, latex, and / or organic binders such as PVA onto the tape backing.
[0043] In any embodiment, the fire-resistant materials described herein can be used to selectively cover 10%-100% of the cell contact surface and can be directly attached to the cell using a hot melt adhesive or a pressure sensitive adhesive. In some embodiments, a combination of the fire-resistant materials described herein (the fire-resistant materials 100, 200 and the fire-resistant films) can be used in a LiB battery pack. In such embodiments, the fire-resistant materials can be placed as needed in the LiB battery pack, for example, between cells or between an array of cells and a housing lid. EXAMPLES
[0044] Comparative Example 1 32.83 g of E-glass microfibers with an average diameter of 0.6 μm were loosened in 3 gallons of water and vigorously stirred until uniformly dispersed. 3.943 mL of 50% anionic acrylic dispersion (Hycar 26083, Lubrizol) was added to the slurry. Finally, 5.65 mL of 5% alum was added to the slurry. The mixture was transferred to a watertight caster on top of a wire mesh screen. A vacuum was applied from below to dewater the slurry through the metal screen. The resulting wet paper was compressed and dried at 65 degrees Celsius.
[0045] The average dry thickness of the paper is 2.59 mm and the density is 162 kg / m 3 Next, the thermal conductivity of the fire protection medium is calculated using a density of 204 kg / m 3 The thermal conductivity was measured according to ASTM C518 and is shown in Table 1 below. EXAMPLES
[0046] Hi-Sil ABS (PPG Industries, Inc.) is a commercially available precipitated silica with an average particle size of 40 μm. 22.44 g of Hi-Sil ABS was dispersed in 3 gallons of water with vigorous stirring. 14.21 g of E-glass microfibers with an average diameter of 0.6 μm were added to the mixing vessel and stirred until uniformly dispersed. 4.26 mL of 50% anionic acrylic dispersion (Hycar 26083, Lubrizol) was added to the slurry. Finally, 6.11 mL of 5% alum was added to the slurry. The mixture was transferred to a watertight caster over a wire mesh screen. A vacuum was applied from below to dewater the slurry through the metal screen. The resulting wet paper was compressed and dried at 65 degrees Celsius.
[0047] The average thickness of the dried composite paper is 2.11 mm and the density is 190 kg / m 3 Next, the thermal conductivity of the fire protection medium is calculated using a density of 250 kg / m 3 The thermal conductivity was measured according to ASTM C518.
[0048] The compression set of the fire protection media of Example 1 and Comparative Example 1 was tested under a modified version of ASTM D3574 Test C. The results are shown in FIG.
[0049] In addition to improving the thermal insulation properties, the compressive properties of this battery pack fire protection material were also improved with the silica additive. Although silica is a brittle, inelastic material, the addition of precipitated silica particles improved the compressive behavior of the material. This is evident from the data shown in Figure 5, where the fiber / silica composite exhibits a greater elastic response under compression compared to the unfilled material of Comparative Example 1.
[0050] Comparative Example 2 92 g of Insulfrax 3010 glass fiber (Alkegen) with fiber index ≥ 70% was loosened in 3 gallons of water and vigorously stirred until uniformly dispersed. 13 mL of 42% cationic acrylic dispersion (Ottopol K-12T, Gellner Industrial) was added to the slurry. The mixture was transferred to a waterproof caster on top of a wire mesh screen. A vacuum was applied from below to drain the slurry through the metal screen. The resulting wet paper was pressed and dried at 65 degrees Celsius.
[0051] Then, the thermal conductivity of the fire protection medium is calculated based on the density of 148 kg / m 3 The thermal conductivity was measured according to ASTM C518. The measured thermal conductivity is shown in Table 1. EXAMPLES
[0052] Hi-Sil ABS (PPG Industries, Inc.) is a commercially available precipitated silica with an average particle size of 40 μm. 46 g of Hi-Sil ABS was dispersed in 2 gallons of water with vigorous agitation. 46 g of Insulfrax 3010 glass fiber with fiber index ≥ 90% (Alkegen) was added to the mixing vessel and agitated until uniformly dispersed. 13 mL of a 43% cationic acrylic dispersion (Ottopol K-12T, Gellner Industrial) was added to the slurry. The mixture was transferred to a waterproof caster over a wire mesh screen. A vacuum was applied from below to dewater the slurry through the metal screen. The resulting wet paper was compressed and dried at 65 degrees Celsius.
[0053] The dried composite paper has an average thickness of 5 mm and a density of 175 kg / m 3 Next, the thermal conductivity of the fire protection medium was calculated based on ASTM C518 with a density of 286 kg / m 3 The measured thermal conductivity is shown in Table 1 below.
[0054] The compression set of the fire protection media of Example 2 and Comparative Example 2 was tested under a modified version of ASTM D3574 Test C. The results are shown in FIG.
[0055] In addition to improving the thermal insulation properties, the compressive properties of this battery pack fire protection material were also improved by the silica additive. Again, even though silica is a brittle, inelastic material, the addition of precipitated silica particles improved the compressive behavior of the material. This is evident from the data shown in Figure 6, where the fiber / silica composite exhibits a greater elastic response under compression compared to the unfilled material of Comparative Example 2.
[0056] Comparative Example 3 In 3 gallons of water, 40.09 g of Isofrax 4010 glass fiber (Alkegen) with fiber index ≥ 85% was loosened and vigorously stirred until uniformly dispersed. 4.22 mL of 50% anionic acrylic dispersion (Hycar 26083, Lubrizoll) was added to the slurry. Finally, 4.22 mL of 5% alum was added to the slurry. The mixture was transferred to a waterproof caster on top of a wire mesh screen. A vacuum was applied from below to dewater the slurry through the metal screen. The resulting wet paper was pressed and dried at 65 degrees Celsius.
[0057] The dried paper has an average thickness of 3.30 mm and a density of 146 kg / m 3 Next, the thermal conductivity of the fire protection medium was calculated based on ASTM C518, and the density was 334 kg / m 3 The measured thermal conductivity is shown in Table 1. EXAMPLES
[0058] In 2 gallons of water, 10.12 g of silicon carbide (particle size 4-7 μm) was dispersed with vigorous stirring. 54 g of Isofrax 4010 glass fiber (Alkegen) with fiber index 85% or higher was added to the mixing vessel and stirred until uniformly dispersed. 6.75 mL of 50% anionic acrylic dispersion (Hycar 26083, Lubrizol) was added to the slurry. Finally, 6.75 mL of 5% alum was added to the slurry. The mixture was transferred to a waterproof caster on top of a wire mesh screen. A vacuum was applied from below to dewater the slurry through the metal screen. The resulting wet paper was compressed and dried at 65 degrees Celsius.
[0059] The dried composite paper has an average thickness of 3.17 mm and a density of 249 kg / m 3 Next, the thermal conductivity of the fire protection medium was calculated based on ASTM C518, and the density was 314 kg / m 3 The measured thermal conductivities are shown in Table 1. The improved compression behavior is shown in Figure 7, where the fiber / silicon carbide composite exhibits a greater elastic response under compression compared to the unfilled material of Comparative Example 3.
[0060] [Table 1]
[0061] As described herein, the fire-resistant material is a controlled compression-resistant material that will withstand the life of the battery cell without affecting the thermal, electrical, and fire-resistant performance of the material. The fire-resistant material described herein can be made thinner than existing technology, thereby maximizing the energy density of the LiB battery pack.
Claims
1. A fire-retardant material comprising: At least 10 wt % inorganic fibers; at least 5 wt. % of an additive dispersed within the inorganic fibers, the additive being selected from fibers, particles, platelets, aerogels, foams, or combinations thereof; At least 2 wt. % of a binder dispersed within the inorganic fibers; having The fire-retardant material, wherein the inorganic fibers, additives, and binders comprise at least 60 wt % of the fire-retardant material.
2. 2. The fire-resistant material of claim 1, wherein the inorganic fibers comprise refractory ceramic fibers (RCF), low biopersistent fibers (LBP), alkaline earth silicate (AES) fibers, polycrystalline wool (PCW), or combinations thereof.
3. 10. The fire-resistant material of claim 1, wherein the additive comprises 5-60 wt. % precipitated silica.
4. 10. The fire resistant material of claim 1, wherein the additive comprises latex, cellulose, silicone, polyvinyl alcohol, organic fiber, or a combination thereof.
5. 5. The fire-resistant material of claim 4 having 5-15 wt% of said binder.
6. 5. The fire-resistant material of claim 4, wherein the binder comprises organic fibers dispersed within the inorganic fibers and heated to bond the fire-resistant material.
7. The fire retardant material according to claim 1, further comprising:
1. A fire-resistant material having 2-50 wt % of a compression additive selected from polyurethane, polyethylene, ethylene propylene diene monomer (EPDM), polyethylene terephthalate (PET), silicone, acrylic latex, organic fibers, or combinations thereof dispersed within said inorganic fibers.
8. A fire protection article comprising: The fire-retardant material according to claim 1 ; a coating layer disposed on at least one surface of the fire-retardant material; having The coating layer is made of bentonite clay, dispersible Al 2 O 3 , a crosslinkable silicone, or a combination thereof.
9. 9. The fire-retardant article according to claim 8, wherein the coating layer is a mixture of polysiloxane, aluminum trihydroxide, magnesium hydroxide, CaCO 3 and an additive selected from expandable vermiculite, fluxing agents, inorganic fibers, wollastonite, mica, aerogel, or combinations thereof.
10. The fire-resistant article of claim 9, wherein the coating layer comprises the fluxing agent and inorganic fibers.
11. 10. The fire-resistant article of claim 9, wherein the coating layer is configured to be cerammed at a temperature of 650 degrees Celsius or greater.
12. 10. The fire-resistant article of claim 9, wherein the coating layer comprises the crosslinkable silicone and is cured using heat or ultraviolet light.
13. A fire protection article comprising: A first layer of the fire-resistant material of claim 1; a compressible layer laminated to the first layer of the fire-resistant material; having the compressible layer comprises polyurethane, polyethylene, ethylene propylene diene monomer (EPDM), polyethylene terephthalate (PET), silicone, acrylic latex, organic fibers, or combinations thereof; A fire-resistant article, wherein the compressible layer does not contain inorganic fibers.
14. 14. The fire-resistant article of claim 13, further comprising: a second layer of fire-resistant material laminated to the compressible layer opposite the first layer of fire-resistant material.
15. 14. The fire-resistant article of claim 13, further comprising: and a coating layer disposed on at least one surface of the first layer of fire-resistant material, the coating layer comprising bentonite clay, dispersible Al. 2 O 3 , a crosslinkable silicone, or a combination thereof.
16. 16. The fire-resistant article of claim 15, wherein the coating layer comprises a fluxing agent and inorganic fibers.
17. 1. A lithium ion battery, A housing having a lid; A plurality of cells housed within the housing; The fire-resistant material of claim 1 disposed between at least two of the plurality of cells or between the plurality of cells and the lid. A lithium-ion battery having
18. 1. A lithium ion battery, A housing having a lid; A plurality of cells housed within the housing; the fire-resistant article of claim 8 disposed between at least two of the plurality of cells or between the plurality of cells and the lid; A lithium-ion battery having
19. 1. A lithium ion battery, A housing having a lid; A plurality of cells housed within the housing; The fire-resistant article of claim 13 disposed between at least two of the plurality of cells or between the plurality of cells and the lid. A lithium-ion battery having
Citation Information
Patent Citations
Battery separator for recombinant batteries
EP0466302A1
Firefighting clothing material
JP2008266841A
Fire-resistant barrier film laminate
JP2010515831A
Multi-layer fireproof material
JP2013510742A
Electrical and thermal protective coating and electrochemical cell containing same
JP2021509690A